Problem behavior in autism spectrum disorders: A paradigmatic self-organized perspective of network structures. (2019) - Tonello, Lucio; Giacobbi, Luca; Pettenon, Alberto; Scuotto, Alessandro; Cocchi, Massimo; Gabrielli, Fabio; Cappello, Glenda
Abstract: Autism spectrum disorder (ASD) subjects can present temporary behaviors of acute agitation and aggressiveness, named problem behaviors . They have been shown to be consistent with the self-organized criticality (SOC), a model wherein occasionally occurring "catastrophic events" are necessary in order to maintain a self-organized "critical equilibrium." The SOC can represent the psychopathology network structures and additionally suggests that they can be considered as self-organized systems.